Middle Class Size in the Past, Present, and Future: A Description of Trends in Asia - Natalie Chun (Asian Development Bank (ADB), 2010)
This paper describes the size of the middle class in developing Asia across countries and over time. Based on an absolute measure of the middle class of 2-20 (2005 purchasing power parity United States dollars), it finds that between 1990 and 2008, the size of the middle class in developing Asia has grown dramatically in percentage share, absolute size, and purchasing power. However, there are large variations in the size and growth of the middle class across countries, with the primary growth of the middle class largely driven by the People's Republic of China (PRC). Considerably smaller growth has occurred in many countries including Nepal and Sri Lanka. Still, a large portion of the middle class residing in the 2-4 range are extremely vulnerable, and many of the poor in Asia remain in the PRC and India. This suggests that it may be good for policymakers to not only focus on countries that have lagged behind in terms of growth of the middle class, but that it should also concern itself with focusing on countries where there is still considerable room to build, and bolster the absolute size of the middle class in Asia.
hdl:11540/4182
Keywords: I30; 330; inclusive growth; developing Asia; middle class; Mittelschicht; Asien